Long-Term Effects of COVID-19 on Optic Disc and Retinal Microvasculature Assessed by Optical Coherence Tomography Angiography - Mine Ozturk; Deniz Kumova Guler; Ekin Ece Oskan; Feyza Onder (Diagnostics)
Objectives: To evaluate the long-term effects of coronavirus disease (COVID-19) on optic disc and macular microvasculature. Methods: 40 post-COVID-19 and 40 healthy subjects were included. Optical coherence tomography angiography (OCTA) was performed for all subjects at the first visit and repeated in the fourth and twelfth months. Radial peripapillary capillary (RPC) vessel density (VD), retinal nerve fiber layer (RNFL) thickness, foveal avascular zone (FAZ) area, FAZ perimeter, VDs of the fovea, parafovea, and perifovea at superficial capillary plexus (SCP) and deep capillary plexus (DCP), and central macular thickness (CMT) were evaluated. The OCTA measurements of the COVID-19 group were compared with the control group. Results: The COVID-19 group showed lower VD values than the control group in the nasal parafoveal quadrant of the SCP at all visits (p = 0.009, p = 0.47, p = 0.042) and in the superior perifoveal quadrant of the DCP in the twelfth-month visit (p = 0.014). At all visits, FAZ area and FAZ perimeter were higher (p = 0.02, p = 0.02, p = 0.002; p = 0.002, p = 0.003, p = 0.005), foveal VD values of both SCP and DCP were lower (p < 0.001, p < 0.001, p < 0.001; p = 0.005, p = 0.001, p = 0.001), and CMT was lower (p < 0.001, p = 0.001, p = 0.001) in the COVID-19 group. The COVID-19 group had higher temporal quadrant RPC at all visits (p = 0.003, p = 0.003, p < 0.001) and higher average, superior and inferior RNFL at first and fourth-month visits (p = 0.014, p = 0.020; p = 0.001, p = 0.003; p = 0.021, p = 0.024). Conclusions: There are long-term changes that mainly point to the ischemia in the COVID-19 patients. We emphasize the need for long-term ophthalmologic and systemic follow-up of COVID-19 patients regarding potential complications.